Effectiveness of Truck Time Restrictions in West Java Industrial Corridor - Pasa, Inda Tri; Prayitno, Hadi; Slamet, Asep Gunawan; Wahyuni, Endang (Logistica : Journal of Logistic and Transportation, 2024)
This study investigates the impact of truck operational time restrictions on traffic safety and congestion in West Java’s industrial corridors. As freight traffic intensifies across key logistic routes such as Cikarang–Karawang, policymakers introduced peak-hour bans on heavy-duty vehicles to alleviate congestion and enhance road safety. Employing a qualitative-descriptive approach, the study collected data through in-depth interviews, field observations, and official reports. Results reveal a dual impact: while congestion and accident rates declined during restricted hours, the policy induced new challenges, including secondary congestion near access points, increased fatigue among night-driving truckers, and unequal compliance among logistics stakeholders. Larger logistics companies successfully adapted by integrating digital scheduling and real-time monitoring, while SMEs encountered structural barriers in policy adaptation due to limited access to technology and information. Inconsistent enforcement and lack of policy awareness also hampered regulatory effectiveness. The discussion emphasizes the need for a balanced approach one that combines regulatory intervention with affirmative support for small-scale actors, and investments in smart enforcement technologies. The findings offer valuable insights for developing inclusive, context-sensitive transport policies in industrially dynamic regions